(untitled) (Biological Sciences - PJSIR, 1996)
An experiment was carried out to study the rate of extraction of the vanadyl ion, V02+ from sulphuric acid medium. The commercial metal extractant, Di ( 2 -ethy hexyl) phosphoric acid (D2EHPA) dissolved in n-hexane diluent was used in the study.The experimental technique was the single drop where the rate of metal extraction was related to the interfacial area for mass transfer. The results showed that the rate of vanadium (IV) extraction was proportional to the aqueous vanadium concentration and the organic concentration of D2EHPA. The rate was also inversely proportional to the aqueous hydrogen ion concentration especially at low acidities. The extraction process had a rate constant of 1.71x IO-4S"at 28°C with an activation energy of 38.75 KJ mole". The system appeared to be controlled by mass transfer with simultaneous chemical reaction.